A Pilot Study Correlation of White Blood Cells Level in Semen with Endometritis in Subfertile Couples - Vellyana Lie; Tiara Kirana; Cynthia Agnes (Universitas Airlangga, 2022)
Introduction Over the past decades, infertility has become a serious health problem worldwide and until nowadays numerous studies have shown it can be a negative prognostic factor for infertility.1 During, natural intercourse, ejaculation of seminal fluid into vagina may deposit spermatozoa, contaminants, and bacteria into the uterus by pelvic or penile thrusting and belling of the glans penis during coitus. In that case, the risk factor of infection in both women and man will happen post natural intercourse. So, the relationship between endometritis and increasing white blood cells level in sperm with infertility such as repeated implantation failure and recurrent miscarriage has recently emerged as an area of inquiry. Aims Aims this study, Correlation of endometritis that found in hysteroscopy examination and increasing white blood cell level in semen in sub fertile couples. Methods This study was conducted from 492 Infertility couple who underwent hysteroscopy from January 2021 to December 2021. The semen analysis was performed at least twice with range two weeks one from the other based on WHO guideline. Hysteroscopy was performed during endometrial proliferation phase. All data analysis performed using IBM SPSS 23. Results The result showed that mean leucocyte level range difference was significant in patient non-endometritis was 0.25 and endometritis patient was 0.66. The leucocyte number had correlation with the result of the pH level and slow progressive motility in semen specimen. Conclusion This research result showed the correlation women with resulted endometritis in hysteroscopy and white blood cell in semen specimen and had correlation with pH level and slow progressive motility in semen specimen. Keywords: White blood cells count in semen, endometritis, subfertil.